Sistem Sosial Ekologi Masyarakat pada Kawasan Kota Baru Mandiri Bukit Semarang Baru (BSB) - Ariani, Nofa Martina; Hadi, Sudharto P (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2016)
The spatial pattern of Semarang illustrate how the pattern that separates the production zone with consumption zone. Consumption zone is where we live, while the production zone is where we work, shop, school prayer, and recreation. The condition causes the townspeople have to commute (nglajo) every day from the residence to the production zone. Patterns of community life of the city brought in a mechanical rhythm of having to use a motor vehicle. Be they as a community-based automobile (Hadi, 2001: 100-101). The existence of these problems lead to the birth of the Self-reliant New Town BSB Semarang. Bukit Semarang Baru (BSB) as an Self-reliant New Town is an integrated spatial planning, where the provision of shelter is equipped with facilities meeting the needs which are within the scope of one area or also called mixed use zoning. To examine changes in activity and mobility of people in urban space integrated pattern which in this case is the Self-reliant New Town BSB then used a socio-ecological systems approach. Socio-ecological systems see the extent of the interaction between different systems. The link between humans and the environment is realized through a variety of physiological processes, psychological and cultural (Lawrence, 2003). The method used in this study is a mix methods with quantitative and qualitative approaches. A quantitative approach is used to analyze the activity and mobility patterns, and a qualitative approach to explain the socio-ecological system of the community. Results from this study that of the five regular activity performed, shopping activities and religious activities have high interaction, because most people have been doing the activity in the region, while for other activities such as the activity of work, school and activity in leisure time is still done in BSB outside the region. The use of public transport modes BSB still choose a long private vehicle.